2016
DOI: 10.1155/2016/6284547
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria Enhance Salinity Stress Tolerance in Okra through ROS-Scavenging Enzymes

Abstract: Salinity is a major environmental stress that limits crop production worldwide. In this study, we characterized plant growth-promoting rhizobacteria (PGPR) containing 1-aminocyclopropane-1-carboxylate (ACC) deaminase and examined their effect on salinity stress tolerance in okra through the induction of ROS-scavenging enzyme activity. PGPR inoculated okra plants exhibited higher germination percentage, growth parameters, and chlorophyll content than control plants. Increased antioxidant enzyme activities (SOD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
134
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(170 citation statements)
references
References 58 publications
14
134
0
6
Order By: Relevance
“…MDA content and plant cell death, that disturb the cell integrity and negatively affect plant growth and development. Similar finding was reported by Khan et al, (2013) in cucumber, Hashem et al, (2016) in Acacia gerrardii, Habib et al, (2016) in okara and Sharifi et al, (2017) (4, ). This is supported by other studies (Kumara et al, 2010;Rawat et al, 2011;Enteshari and Sharifian, 2012;Weizhen and Lei, 2013;Zhang et al, 2016).…”
Section: Plant Cell Deathsupporting
confidence: 90%
“…MDA content and plant cell death, that disturb the cell integrity and negatively affect plant growth and development. Similar finding was reported by Khan et al, (2013) in cucumber, Hashem et al, (2016) in Acacia gerrardii, Habib et al, (2016) in okara and Sharifi et al, (2017) (4, ). This is supported by other studies (Kumara et al, 2010;Rawat et al, 2011;Enteshari and Sharifian, 2012;Weizhen and Lei, 2013;Zhang et al, 2016).…”
Section: Plant Cell Deathsupporting
confidence: 90%
“…In our study, MLR6 improved the chlorophyll content in A. thaliana , confirming previous studies showing that PGPR‐inoculated plants exhibited a higher chlorophyll content (Habib et al . ; Sapre et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compatible osmolytes induced in plants by microbial strains in response to salinity stress lead to promote plant growth. Recently, several studies demonstrated that the application of PGPR can significantly improve plant tolerance to salt stress (Egamberdieva and Lugtenberg 2014;Bharti et al 2016;Habib et al 2016;Sapre et al 2018). In this way, micro-organisms present in the saline area or in the rhizosphere of halophytic plants may provide a valuable resource to improve crop tolerance to salinity (Vaishnav et al 2016) since inoculants isolated from indigenous salt-affected soils appeared more effective in application under saline regions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that certain beneficial bacteria alleviated salt stress of okra. Enterobacter promoted growth and enhanced antioxidant production in salt stressed okra plants (Habib et al 2016). Further studies are necessary to determine the mechanisms by which B. amyloliquefaciens increases salt stress tolerance of its hosts and the long-term effects of inoculating B. amyloliquefaciens onto cotton and okra seeds.…”
Section: Seed Rhizosphere and Systemic Colonization Of Cotton Seedlimentioning
confidence: 99%